1986
DOI: 10.1002/app.1986.070310816
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of talc‐filled polyethylene and nylon 6 films

Abstract: SynopsisWater vapor transmission rates can be reduced by as much as 50% in polyethylene by using talc as a filler. The oxygen permeability as well as water vapor transmission rates are similarly reduced by talc in nylon 6 films. The films show low elongation at break and reduced breaking strength in the presence of talc. The yield strength and the modulus increase with the amount of talc, whereas the elongation at yield decreases. The mechanical and the barrier properties change with the size of the filler, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…[11] Talc overcomes this disadvantage by better dispersion in the polymer matrix and providing the tortuous path to permeant gas molecules and retard the diffusion of the gas molecules through the matrix. [15,23] The oxygen permeability of PLA/PCL blend and its talc reinforced composites was studied as a function of talc concentration and given in Figure 13. It was studied that addition of talc into PLA/PCL blend results in a significant improvement in oxygen barrier properties of PLA/PCL/talc composites.…”
Section: Oxygen Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[11] Talc overcomes this disadvantage by better dispersion in the polymer matrix and providing the tortuous path to permeant gas molecules and retard the diffusion of the gas molecules through the matrix. [15,23] The oxygen permeability of PLA/PCL blend and its talc reinforced composites was studied as a function of talc concentration and given in Figure 13. It was studied that addition of talc into PLA/PCL blend results in a significant improvement in oxygen barrier properties of PLA/PCL/talc composites.…”
Section: Oxygen Permeabilitymentioning
confidence: 99%
“…[21] Addition of talc improves the mechanical properties of the composites; however, elongation at break and break strength decreases with the addition of talc [22,23] and tensile modulus increases with the amount of talc. [23] Talc-filled PLA composites was studied and reported to improve flexural, tensile, and impact properties compared to those of neat PLA. [24,25] Talc also increases the heat deflection temperature (HDT) of the PLA.…”
mentioning
confidence: 99%
“…It has been shown that large amounts of macro-sized and micro-sized fillers are required in order to see a significant change in the desired physical or mechanical properties [12][13][14]. The macro-sized and micro-sized fillers lack an intense interaction within the polymer matrix due to the limited interfacial area.…”
Section: Introductionmentioning
confidence: 99%
“…The development of composite materials with high strength, high modulus and low density by incorporating fillers such as silica [6][7][8][9][10][11], short glass fibers [12,13], talc, mica [14] and graphite [15] in the polymer matrix has been studied extensively. It has been shown that large amounts of macro-sized and micro-sized fillers are required in order to see a significant change in the desired physical or mechanical properties [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Alternating lamellar structures having potentially barrier characteristics may be produced by microlayer coextrusion [2]. Examples of processes favoring flow induced orientation of inorganic platelets are coextrusion blow molding of bottles, or blow film coextrusion for mica filled EVOH resins [18], blown film extrusion for PA-6 or PE films containing talc [19,20], extrusion blow molding of HDPE/talc bottles [21], and injection molding of thin PP/talc or PP/Nylon/talc composites [15]. This last approach has been used to produce polypropylene (PP)/EVOH and polyethylene (PE)/PA-6 ribbons extruded through special dies with converging and diverging sections [4 to 7], LDPE/EVOH blown films [8,9], blow molded high barrier fuel tanks, and containers from polyolefin/polyamide/compatibilizer mixtures with improved barrier characteristics to hydrocarbons, automotive fluids and oxygen [10 to 15].…”
Section: Introductionmentioning
confidence: 99%